The Western Sierras Pampeanas: Protracted Grenville-age history (1330-1030 Ma) of intra-oceanic arcs, subduction-accretion at continental-edge and AMCG intraplate magmatism - Rapela, Carlos Washington (2010)
New U–Pb SHRIMP zircon ages combined with geochemical and isotope investigation in the Sierra de; Maz and Sierra de Pie de Palo and a xenolith of the Precordillera basement (Ullun), provides insight into; the identification of major Grenville-age tectonomagmatic events and their timing in the Western Sierras; Pampeanas. The study reveals two contrasting scenarios that evolved separately during the 300 Ma long; history: Sierra de Maz, which was always part of a continental crust, and the juvenile oceanic arc and; back-arc sector of Sierra de Pie de Palo and Ullun. The oldest rocks are the Andino-type granitic orthogneisses; of Sierra de Maz (1330–1260 Ma) and associated subalkaline basic rocks, that were part of an; active continental margin developed in a Paleoproterozoic crust. Amphibolite facies metamorphism; affected the orthogneisses at ca. 1175 Ma, while granulite facies was attained in neighbouring meta-sediments; and basic granulites. Interruption of continental-edge magmatism and high-grade metamorphism; is interpreted as related to an arc–continental collision dated by zircon overgrowths at 1170–1230 Ma.; The next event consisted of massif-type anorthosites and related meta-jotunites, meta-mangerites; (1092 ± 6 Ma) and meta-granites (1086 ± 10 Ma) that define an AMCG complex in Sierra de Maz. The; emplacement of these mantle-derived magmas during an extensional episode produced a widespread; thermal overprint at ca. 1095 Ma in neighbouring country rocks. In constrast, juvenile oceanic arc and; back-arc complexes dominated the Sierra de Pie de Palo–Ullun sector, that was fully developed ca.; 1200 Ma (1196 ± 8 Ma metagabbro). A new episode of oceanic arc magmatism at 1165 Ma was roughly; coeval with the amphibolite high-grade metamorphism of Sierra de Maz, indicating that these two sectors; underwent independent geodynamic scenarios at this age. Two more episodes of arc subduction are; registered in the Pie de Palo–Ullun sector: (i) 1110 ± 10 Ma orthogneisses and basic amphibolites with; geochemical fingerprints of emplacement in a more mature crust, and (ii) a 1027 ± 17 Ma TTG juvenile; suite, which is the youngest Grenville-age magmatic event registered in the Western Sierras Pampeanas.; The geodynamic history in both study areas reveals a complex orogenic evolution, dominated by convergent; tectonics and accretion of juvenile oceanic arcs to the continent.